Evidence of High-Shear-Velocity Anomalies Inside the Pacific LLSVP - Rafael Abreu; Mariano S. Arnaiz-Rodríguez; Chahana Nagesh (Geosciences)
We present the evidence of high-velocity regions within the Pacific Large Low Seismic Velocity Province (LLSVP), uncovered using the Virtual Receiver Approach (VRA), a novel seismic imaging method that allows us to determine local absolute velocity values of a non-reflecting body wave that are independent of any assumed Earth model. Our results reveal a complex dynamics of high- and low-velocity regions within the Pacific LLSVP. While low-shear-wave velocities dominate, consistent with the traditionally understood nature of LLSVPs, we identify distinct high-velocity anomalies—an observation not previously reported in this region. We interpret these anomalies as lateral compositional variations within the LLSVP. Petrological modeling suggests that high-velocity regions are associated with low FeO content, potentially linked to the inclusion of post-perovskite material driven by mantle convection. Alternatively, remnants of subducted oceanic crust (e.g., Mid-Ocean Ridge Basalts) could also explain the observed features. Conversely, low-velocity anomalies correspond to FeO-rich compositions. Our findings highlight the thermochemical heterogeneity of the LLSVP, revealing a more complex internal structure than previously thought. The application of the VRA is able to resolve fine-scale structures that have remained as some of the biggest challenges in global tomographic models.